Diseño mecánico de una secadora de contra-flujo - Ives, N.C. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Laboratory scale equipment and procedure were developed to simulate several of the many possible through circulation type forced-heated air systems for drying coffee. Tests were designed to investigate the effect of various drying systems and entering air temperatures on the resultant cup quality of coffee, and to obtain drier design data and performance characteristics.